KEWENANGAN KOMISI INFORMASI DALAM MENGADILI SENGKETA INFORMASI PUBLIK (Studi Kasus: Forum Diskusi Suporter Indonesia melawan Persatuan Sepak Bola Seluruh Indonesia) - Angretta Lolita; Muhammad Abudan (Jurnal Hukum Adigama, 2018)
Public information should be accessible to everyone. Information must be disclosed to the public without any limitation and transparent. Right of Information becomes very important along with more transparent state administration for public supervision and more accountable state administration. Upon enactment of Law Number 14 of 2008 on Public Disclosure, Information in the governmental public agency becomes more transparent. Public Disclosure may also over time create problems inspiring the establishment of Information Commission. Information Commission is the only agency vested with the authority to resolve Public Information Dispute. No other governmental agency or body is vested with the same authority. This is termed absolute authority of the Information Commission in resolving Public Information Dispute. However, in reality, Information Commission is proven unfair and acting beyond its authority in Decree Number 199/VI/KIP-PS-A/2014. How the Information Commission acts beyond is authority? The author examined the issue by normative method. The data of research show the weakness of the Information Commission in resolving Information Dispute. This weakness results in legal uncertainty. Information Commission must immediately evaluate the fault in such dispute.